ANALISIS UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974 DALAM PENETAPAN WALI - Muhammad Sibawaih; Rasfiudin S (JURNAL CERDAS HUKUM, 2022)
Research on the analysis of guardians in marriage according to the law or positive law is very important to be studied comprehensively. This is because the matter of marriage in principle is also regulated in the rules of Islamic religious law. The results of this study will later see how the position of marriage guardians for women in the review of legislation, especially Law no. 1 of 1974 concerning Marriage. And who is the guardian referred to by Law no. 1 of 1974. This research uses normative juridical or research that prioritizes data reference to library documents. Normative method approach and literature review in this study. It also focuses on finding the legal basis for guardianship in Law no. 1 of 1974. The results of this study indicate that the guardian referred to in Law no. 1 of 1974 is the same guardian in the perspective of Islamic law, the guardians include father, paternal grandfather, biological brother, biological uncle, biological cousin, sultan or judge, guardian who is appointed directly by the bride who want to get married.